2015
DOI: 10.7314/apjcp.2015.16.5.1935
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Participation of the GSTM1 Polymorphism in Cervical Cancer Development in Northeast Thailand

Abstract: The potential association between the GSTM1 deletion polymorphism and risk of cervical cancer was investigated in Northeastern Thailand. DNA was extracted from buffy coat specimens of 198 patients with squamous cell carcinoma of the cervix and 198 age-matched healthy controls. Genotyping of the GSTM1 was conducted by using two PCR methods, a short-and a long-PCR. Distribution of the GSTM1 genotypes in between the cases and the controls was not significantly different (p>0.5 by χ 2 test). The results suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Another more recent meta-analysis revised and updated the data of the Chinese population and found a significant association between GSTM1 null polymorphisms and cervical cancer in that population (Sun and Song, 2016). Disagreement between published results can be explained mainly by the different frequencies of this polymorphism in different populations, which can vary from 26% in Africans to 53% in Caucasians (Natphopsuk et al, 2015). Additionally, other factors could be associated with cancer development, such as lifestyle and exposition to different environmental xenobiotics.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another more recent meta-analysis revised and updated the data of the Chinese population and found a significant association between GSTM1 null polymorphisms and cervical cancer in that population (Sun and Song, 2016). Disagreement between published results can be explained mainly by the different frequencies of this polymorphism in different populations, which can vary from 26% in Africans to 53% in Caucasians (Natphopsuk et al, 2015). Additionally, other factors could be associated with cancer development, such as lifestyle and exposition to different environmental xenobiotics.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study developed in Thailand concluded that deletion of GSTM1 is not a risk factor for cervical cancer. This study seems to present higher accuracy, since not only the null genotype for GSTM1 was studied but also the heterozygous variables for this gene (Natphopsuk et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…21 studies of GSTM1 polymorphisms (2,250 CC cases and 3,025 controls) [6,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] , 17 studies of GSTT1 polymorphisms (1,704 CC cases and 2,060 controls) genotypes [6, 11-13, 15-17, 20-24, 26-30] , and 9 studies of GSTM1-GSTT1 interaction analyses (1,046 CC cases and 1,319 controls) [6,11,12,15,16,24,26,28] were included in our meta-analysis. The characteristics of the studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that individuals with the GSTM1 null genotype lack the functional ability to detoxify the ultimate form of carcinogens and are, therefore, susceptible to cancer in various organs (including the lung, bladder, oral and nasopharynx) (Schnakenberg et al, 2000;Shield PG., 2002;Tiwawech et al, 2005;Liu et al, 2014;Zakiullah et al, 2015). Results of many other studies dealing with the association between GSTM1 polymorphism in some of these cancers have, however, proven contradictory (Tanimoto et al, 1999;Hahn et al, 2002;Natphopsuk et al, 2015). Geographical and ethnic differences as well as the method of genotypic detection may be responsible for the apparently conflicting data.…”
Section: Preliminary Study Of the Gstm1 Null Polymorphism And History Of Tobacco Smoking Among Oral Cancer Patients In Northeastern Thailmentioning
confidence: 99%
“…GSTM1 genotype was determined by the two independent PCR assays described by Natphopsuk et al (2015). To identify the GSTM1 null allele, a short-PCR amplification (Tiwawech et al, 2005) was performed using a primer pairs (5'-GAA CTC CCT GAA AAG CTA AAG C-3' and 5'-GTT GGG CTC AAA TAT ACG GTG G-3'); an amplification of the β-globin was used as an internal control.…”
Section: Detection Of Gstm1 Polymorphismmentioning
confidence: 99%